A cylindrical magnetically-actuated drug delivery device proposed for minimally invasive treatment of prostate cancer. Issue 119 (17th November 2015) - Zachkani, P.; Jackson, J. K.; Pirmoradi, F. N.; Chiao, M.
Abstract : A cylindrical magnetically-actuated MEMS drug delivery device, implanted through a needle for localized prostate cancer treatment is proposed. Abstract : A cylindrically shaped magnetically-actuated MEMS (microelectromechanical systems) drug delivery device for localized prostate cancer treatment is proposed in this work. The device is designed for implantation through a gauge 12 needle for minimally invasive procedures. The drug delivery device consists of a drug reservoir, a PDMS (polydimethylsiloxane) membrane, a magnetic block and a housing. Under external magnetic fields, the movement of the magnetic block deflects the membrane and discharges the drug through an aperture and into the housing. The housing has a large opening which allows the released drug to diffuse to the surrounding tissues while it prevents the tissues from touching the membrane. On-demand drug release with consistent release rates and device implantation using a needle into ex vivo porcine bladder tissue are demonstrated.